2015
DOI: 10.1515/tlr-2015-0008
|View full text |Cite
|
Sign up to set email alerts
|

The differential representation of number and gender in Spanish

Abstract: This paper investigates the geometry of phi-features with a special emphasis on number and gender in Spanish. We address (i) whether number and gender evidence single-or multi-valued systems for their respective features, and (ii) whether number and gender are bundled together or split. Given the lack of consensus on these issues based on primary data, we approach these questions experimentally, using the phenomenon of agreement attraction: a situation in which ungrammatical sequences are perceived as grammati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
46
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(54 citation statements)
references
References 37 publications
7
46
1
Order By: Relevance
“…Under a bundling model, number and gender are bundled together and therefore leveled-there is no clear hierarchical relationship between the features that could deliver a consistent linear order. With arguments in favor of both the bundled model and the split model, the task is to determine which model is appropriate for which language-it need not be the case that every language approaches number and gender features in the same way (for a discussion of yet more arguments, see Fuchs et al 2015 and the references therein). In Fuchs et al (2015), we used experimental evidence from agreement phenomena to establish the baseline feature representation and specification in the native Spanish grammar.…”
Section: Background: Feature Representation In the Native Spanish Basmentioning
confidence: 99%
See 2 more Smart Citations
“…Under a bundling model, number and gender are bundled together and therefore leveled-there is no clear hierarchical relationship between the features that could deliver a consistent linear order. With arguments in favor of both the bundled model and the split model, the task is to determine which model is appropriate for which language-it need not be the case that every language approaches number and gender features in the same way (for a discussion of yet more arguments, see Fuchs et al 2015 and the references therein). In Fuchs et al (2015), we used experimental evidence from agreement phenomena to establish the baseline feature representation and specification in the native Spanish grammar.…”
Section: Background: Feature Representation In the Native Spanish Basmentioning
confidence: 99%
“…To investigate the content of heritage speakers' knowledge about their morphology, together with the pressures that could shape differences in that knowledge relative to the native baseline, here we extend the experimental methodology developed in Fuchs et al (2015) to examine number and gender agreement in heritage Spanish. We focus on number and gender features because they are expressed on independent exponents in the native Spanish grammar, and because theoretical approaches to the structure of these categories provide two analytical possibilities for their representation in syntax.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As is well known all nouns are assigned one of two possible formal Genders in Spanish, either the so-called 'masculine' or the 'feminine', which are more or less evenly distributed within the set of nouns (Fuchs et al 2015). One of the traditionally assumed functions of Gender, or noun class, is that of concord controller (see Hockett 1958;Corbett 1991;Corbett & Fraser 2000).…”
Section: Gender Marking In Spanish a Short Surveymentioning
confidence: 99%
“…Behavioral experiments in language production and comprehension have shown that the two categories have different syntactic representation and different processing loci. See Fuchs et al (2015) and all references cited there for a recent overview and discussion of the evidence. 12 Note that the pluralia tantum expression sus pantalones 'his/her trousers' in the antecedent of example (15 a) refers to one piece of clothing, not many.…”
Section: Inherent/lexical Numbermentioning
confidence: 99%